A potential microbial control for fireweed (Epilobium angustifolium) - Winder, R.S.; Watson, A.K. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1994)
Diseased fireweed (Epilobium angustifolium) plants were collected in Quebec and organisms isolated from these plants were evaluated as potential biocontrol agents. Thirteen pathogenic fungi were isolated and three of these (Colletotrichum dematium, Seimatosporium kriegerianum, and Alternaria alternata) were virulent in initial screening assays. C. dematium was selected for further study because it was the most virulent pathogen, causing large necrotic lesions on leaves and stems of infected plants. Inoculum production was optimized on modified malt extract agar and the virulence enhanced by suppression of the conidial matrix with tannic acid and the addition of extracts of Aloe saponaria. The fungus was pathogenic to fireweed and E. lanceolatum, while other test species were very resistant or immune. Measurements of conidial and appressorial dimensions and its restricted host range support the hypothesis that the isolate may be an unreported form-species. Application of formulated conidia consistently provided 100% mortality of 7-wk-old inoculated fireweed rosettes within 48 h using 109 conidia m-2, from 10- to 15-d-old inoculum, and a 18- to 24-h dew period. Virulence was diminished in older plants. In field trials, growth of inoculated rosettes was reduced by 33%. These results suggest that C. dematium is a promising candidate for further development as a control agent for seedling fireweed in silviculture.